HUBUNGAN ANTARA KARAKTERISTIK INDIVIDU DAN FAKTOR PEKERJAAN TERHADAP KELUHAN LOW BACK PAIN PADA PEKERJA AGEN LPG DI KELURAHAN MANGGARAI JAKARTA TAHUN 2020 - Salma Devita Oktavia (2020)
Based on observations most of the workers at the LPG agent in Manggarai Subsdistric handle gas cylinders manually for about 8 hours and the frequency of activities undertaken by workers is very high. Based on the initial interviews, most of the workers have experienced pain in their lower back. This can increase tension in the muscles and cause disability. The aim of this study was to determine the relationship between individual characteristics and occupational factors with low back pain complaints among LPG agent workers at Kelurahan Manggarai Jakarta in 2020. This research used a cross sectional study design. A total of 52 workers were recruited by using a total sampling technique. Data were analyzed using the Chi-Square test. Workers' body positions were observed by adjusting the OWAS observation assessment sheet. The results of the analysis found that age, BMI, smoking habits, manual material handling and years of work have a significant relationship with LBP complaints (p-value <0.05), whereas physical activity does not have a significant relationship with LBP complaints (p-values >0.05). The company should create a two-wheeled hand truck based on worker anthropometry to minimize LBP complaints.